Africa : Irrigation investment Needs in Sub-Saharan Africa - You, Liang Zhi (Washington, DC, World Bank, 2012)
In Sub-Saharan Africa, rainfall is highly variable and, in many places, plainly in sufficient. Although irrigation has the potential to boost agricultural yields by at least 50 percent, food production in the region is almost entirely rain-fed. The irrigated area, extending over 6 million hectares, makes up just 5 percent of the total cultivated area, compared to 37 percent in Asia and 14 percent in Latin America. Two-thirds of that area is in three countries: Madagascar, South Africa, and Sudan. The 2005 Commission for Africa report, for example, called for a doubling of the region's irrigated area by 2015. To achieve expansion on that scale, however, we must deepen our understanding of the locations that could benefit most-and of the technologies best suited to those locations. One purpose of this study of irrigation in 24 countries, undertaken as part of the Africa infrastructure country diagnostic, is to identify agricultural areas, where irrigation investments promise to yield significant returns. A related purpose is to estimate the amount and scope of investment needed to secure those returns. Water for irrigation can be collected in two ways: through large, dam-based schemes, or through small projects based on collection of run-off from rainfall.